The importance of the Pacific Alliance - Barrientos Felipa, Pedro (2015)
The Pacific Alliance is a new initiative for integration in Latin America. It is part of the process that drives globalization in search of a better use of the opportunities presented in the international market. Opportunities provided by new production processes, which represents a challenge: moving from a primary exporting country to an exporting country with higher value added. Take advantage of what you have and learn to keep growing. This article explains the commitment that the countries to advance towards a new stage and should be harnessed for the equal benefit of their economic operators.